Arsitektur Sistem Point of Sale (POS) Multi-Cabang Berbasis Web untuk Perusahaan Ritel Terdistribusi: Studi Kasus pada Raffi Collection - Mardhatillah; Aldo Erianda; Ronal Hadi (SOTVI - Society of Visual Informatics, 2026)
In the modern retail ecosystem, managing distributed store operations through manual interventions presents critical vulnerabilities regarding data consistency, synchronization delays, and operational inefficiencies. This research addresses these systemic limitations by designing and implementing a web-based, centralized Multi-Branch Point of Sale (POS) system tailored for Raffi Collection, a retail enterprise managing three geographically dispersed branches in Bukittinggi. Adopting the structured Waterfall development methodology—encompassing requirements analysis, system design, implementation, testing, and maintenance—the platform was engineered utilizing the Laravel MVC framework and a centralized MySQL relational database management system. The system architecture incorporates a robust Role-Based Access Control (RBAC) mechanism defining distinct operational permissions for Super Admins and Branch Admins. Key functional workflows feature real-time transaction processing with automated cryptographic-like receipt string generation, an advanced cross-branch stock transfer approval workflow, and dynamic multi-criteria reporting engines covering sales, expenditures, inventory mutations, and net profit-loss analytics. Empirical system testing validated absolute data synchronization across all nodes, strict enforcement of security policies (demonstrated by automated 403 Access Denied responses to unauthorized routing), and precise financial auditing capability. The implementation effectively eliminates data redundancy, mitigates recording latencies, and provides business stakeholders with real-time, data-driven decision support tools